The Quantum age - Lemire, Jeff (Dark Horse Books, 2019)
"In the world of the Eisner Award-winning Black Hammer series--but a thousand years in the future--a collection of superheroes, inspired by the legendary heroes of Black Hammer Farm, must band together to save the planet from an authoritarian regime. A young Martian must find a way to reform The Quantum League to save the world, while solving the riddle of what happened to the great heroes of the twentieth century"--